First high resolution analysis of the 3ν2 and 3ν2−ν2 bands of 32S16O2; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 202 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Beryozkin K. B. Kirill Borisovich; Horneman V. M. Veli Matti; Sydow C. Christian; Maul C. Christof; Bauerecker S. Sigurd (2017, 2017)
Title screen